Modern Arabic literature : a theoretical framework - Snir, R. (Reuven) (Edinburgh University Press, 2017)
The study of Arabic literature is blossoming. This book provides a comprehensive theoretical framework to help research this highly prolific and diverse production of contemporary literary texts. Based on the achievements of historical poetics, in particular those of Russian formalism and its theoretical legacy, this framework offers flexible, transparent, and unbiased tools to understand the relevant contexts within the literary system. The aim is to enhance our understanding of Arabic literature, throw light on areas of literary production that traditionally have been neglected, and stimulate others to take up the fascinating challenge of mapping out and exploring them.